NITROGEN, BORON AND AMINO ACID LEVELS IN THE NEEDLES OF SCOTS PINE SEEDLINGS WITH CONTROLLED NITROGEN AND BORON SUPPLY - Nadezhda Chernobrovkina; Elena Robonen (Transactions of the Karelian Research Centre of the Russian Academy of Sciences, 2016)
The content of nitrogen, boron and free amino acids were studied in needles of Scots pine (Pinus sylvestris L.) seedlings as related to variations in nitrogen and boron availability. Interrelated effects of nitrogen and boron on the amino acid composition in needles were identified. Boron content in needles rose in line with boric acid dosage, and application of nitrogen reduced boron levels in needles. The high nitrogen and the optimal boron doses enlarged the content of total and protein nitrogen and total free amino acids in needles. Nitrogen applications in combination with three different levels of boron availability mainly raised arginine levels, but also promoted the content of ornithine and lysine. The content of OH-lysine, glutamic and aspartic acids, alanine, serine, threonine, proline and methionine in needles increased when boron was deficient, and rose when boron supply was optimal. Optimization of boron nutrition in low nitrogen settings raised total free amino acid content in needles owing to a rise in glutamic and aspartic acids, alanine and OH-lysine, whereas in high nitrogen settings the rise was mainly owing to arginine. Phenylalanine  and tyrosine levels in the latter case also rose, but the levels of the rest of amino acids declined. Application of the high dose of boric acid against two nitrogen backgrounds in- duced a reduction or a downward trend in the content of all forms of nitrogen and a major- ity of free amino acids in needles, except for cysteine in a simultaneous low- and proline in a high nitrogen treatment.